Analysis of Digital Governance Implementation in Land and Building Tax Management - Wahyudin, Cecep; Munjin, R. Akhmad; Zidane, Muhammad Rafi Diaz (Kolaborasi : Jurnal Administrasi Publik, 2025)
Digital transformation in public services has become an urgent necessity to meet demands for efficiency, transparency, and the optimization of regional revenue. This study aims to analyze the implementation of digital governance as a strategy to increase Land and Building Tax (PBB) revenue at the Regional Revenue Agency (Bapenda) of Bogor City. The urgency of this research lies in the need to integrate digital technology into the regional taxation system to address challenges such as digital literacy, public participation, and inefficiencies in conventional systems. This research uses a quantitative approach. The theoretical framework used is the digital governance framework, which includes three dimensions: digital strategy, digital policy, and digital standards. The results show that the implementation of digital governance at Bapenda Bogor is categorized as “good,” with an average score of 3.83 from employees and 3.56 from taxpayers. A significant increase in PBB revenue was recorded following the digitalization of E-SPPT, as indicated by tax realization surpassing the targets from 2021 to 2024. The main obstacles lie in public digital literacy, limited human resources, and a lack of outreach. The novelty of this research lies in its integrative approach, linking SPBE regulations, local digital strategies, and the practical application of tax services through the E-SPPT platform. This study provides both theoretical and practical contributions to the development of more inclusive, sustainable, and responsive digital policies at the regional level.